(untitled) (Collaborate Engineering Daily Book Series, 2024)
This study examines the environmental challenges associated with shipwreck removal from the perspective of the International Convention for the Prevention of Pollution from Ships (MARPOL). Shipwrecks pose significant risks to marine ecosystems, navigation, and human activities, yet their removal process can also lead to substantial environmental disturbances. This research analyzes current practices of shipwreck removal, their environmental impacts, and their alignment with MARPOL regulations through a comprehensive mixed-method approach. The methodology combines systematic literature review, analysis of five recent shipwreck removal case studies, and semi-structured interviews with ten maritime experts. The findings reveal critical environmental challenges including hazardous material releases, habitat destruction, noise pollution, and sediment disturbance. While MARPOL provides a framework for preventing ship-based pollution, its application to shipwreck removal operations often lacks clarity and consistency. The study identifies successful innovative approaches in recent projects, such as pre-removal oil extraction and containment barrier deployment, which demonstrate the feasibility of environmentally responsible removal practices. Based on these findings, the research proposes recommendations for enhancing environmental protection during shipwreck removal operations, including developing specific MARPOL guidelines, implementing mandatory environmental impact assessments, and strengthening monitoring mechanisms. These measures aim to balance the necessity of wreck removal with environmental preservation requirements under MARPOL regulations.